Profile of Melasma Patients: A Retrospective Study - Alfrid Asditya; Hari Sukanto (Faculty of Medicine, Universitas Airlangga, 2017)
Background: Melasma is a common hypermelanotic condition that can be frustrating to patients, thus appropriate diagnosis and management of melasma is required. Purpose: To evaluate patient’s profile, diagnosis, and management of melasma. Methods: Retrospective study of new patient in Cosmetic Division, Dermatology and Venereology Outpatient Clinic Dr. Soetomo General Hospital, Surabaya from January 2011 until December 2013. Result: Total new patient of melasma in Cosmetic Division, Dermatology and Venereology Outpatient Clinic, Dr. Soetomo General Hospital, Surabaya from January 2011 until December 2013 (3 years) is 869 patients. Conclusion: Appropriate diagnosis, treatment, and education is needed to manage melasma because of the chronicity and progressivity of this disease.